PERANCANGAN AUGMENTED REALITY BERBASIS ANDROID SEBAGAI PROMOSI TAMAN SRIWEDARI SURAKARTA - Widayaningsih, Nur Hanifati; Handriyotopo, Handriyotopo (CITRAWIRA : Journal of Advertising and Visual Communication, 2020)
Taman Sriwedari Surakarta is a cultural heritage treasure that needs efforts to preserve and introduce historical buildings and cultural values to the public, especially young people, through Android-based augmented reality technology. The purpose of this design is that the public can enjoy historical videos, exterior buildings, and the revitalization of the 2018 Surakarta Sriwedari Park video based on android. The design of Augmented Reality becomes more attractive, interesting, and educational as well as a means of preserving Surakarta Sriwedari Park as a cultural heritage. This design uses the diffusion analysis of innovation, the Multimedia Development Live Cycle method, layout design, selection of typography and colors that have aesthetic values. The results of this design are in the form of identity creation, a catalog book containing markers and information, and an application called SriwedARi. An advertising promotion strategy in an effort to introduce this product uses above and below the line media as well as through online stores. Keyword: Taman Sriwedari Surakarta, Augmented Reality, diffusion of innovation, marker.